Upaya Pembiasaan Shalat Berjamaah Dalam Menumbuhkan Sikap Disiplin Siswa SMPN 1 Wonosalam Jombang - Wahyudi, Imam Shobirin; AM., Supriadi (STAI Asy-Syukriyyah, 2024)
This study examines the cultivation of discipline through the habit of praying in congregation among students of SMPN 1 Wonosalam, Jombang. The research uses a qualitative approach with the type of case study research (case study). Data collection was carried out using interview techniques, observation and documentation to obtain data regarding the implementation of the habituation of congregational prayers in increasing student discipline. The data analysis techniques used data reduction techniques, presentation and drawing conclusions. However, there are inhibiting factors, namely students who are slightly encouraged and supervised, there is envy from students of religions other than Islam, there are prayer shifts that make it lazy to queue, and the lack of parental supervision in terms of the habit of obligatory prayers when students are at home. Overall, this study emphasizes the importance of discipline for life at school and outside school with the habit of praying in congregation.